Relationship between suicide and responsible factors among undergraduates, University of Ilorin, Ilorin, Nigeria - Ibrahim, Ologele; Abiodun, Stephen Joseph; Garba, Isiaka; Oyeyinka, Abraham Jide; Olugbenga, Ilutonmihi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Suicide is a public health problem that causes premature death among youths worldwide. Therefore, the study investigated the factors responsible for suicide among youths as expressed by undergraduate of the University of Ilorin, Ilorin, Nigeria. The objectives of the study were to determine the relationship between suicide and responsible factors based on ; substance abuse, mental illness and stress among Undergraduates in University of Ilorin, Ilorin, Nigeria. Descriptive research design of the survey was used for the study. The population of the study comprises of all the undergraduate registered in 2018/2019 academic session. The target population comprised of all the twenty-three thousand and fifty (23,050) undergraduates from the six selected faculties in the University of Ilorin. A multi-stage sampling technique that made up of simple, proportionate, purposive and convenience sampling techniques were used to select six hundred and ninety-two (692) respondents participated in the study. Researcher developed questionnaire that had been validated by 3 experts from the related field was used for the study. The reliability of the instrument ascertained through test re-test method using Pearson Product Moment Correlation (PPMC), a correlation coefficient of 0.80r was obtained. The researcher administered the instrument with the help of three trained research assistants. Inferential statistic of Pearson Product Moment Correlation was used to analyse the result of data collected at 0.05 level. The findings revealed that substance abuse, mental illness and stress were responsible factors for suicide among undergraduates in the study area. Evidence derived from the study also suggest implication for the University authority in relation to enlight Undergraduates on responsible factors associated with suicide.